High Fat Diet Decreases Beneficial Effects of Estrogen on Serotonin-Related Gene Expression in Marmosets - Bethea, Cynthia L (Prog Neuropsychopharmacol Biol Psychiatry, 2014)
The administration of estradiol-17β (E) to animal models after loss of ovarian steroid production has many beneficial effects on neural functions, particularly in the serotonin system in nonhuman primates (NHPs). E also has anorexic effects, although the mechanism of action is not well defined. In the US, obesity has reached epidemic proportions, and blame is partially directed at the Western style diet, which is high in fat and sugar. This study examined the interaction of E and diet in surgically menopausal nonhuman primates with a 2 × 2 block design. Marmosets (Callithrix jacchus; n=4/group) were placed on control-low fat diet (LFD; 14%kcal from fat) or high fat diet (HFD; 28%kcal from fat) 1 month prior to ovariectomy (Ovx). Empty (placebo) or E-filled Silastic capsules were implanted immediately following Ovx surgery. Treatments extended 6 months. The established groups were: placebo+LFD; E+LFD; placebo+HFD, or E+HFD. At necropsy, the brain was flushed with saline and harvested. The midbrain was dissected and a small block containing the dorsal raphe nucleus was processed for qRT-PCR using Evagreen (Biotinum). Genes previously found to impact serotonin neural functions were examined. Results were compared with 2-way ANOVA followed by Bonferroni post-hoc tests or Cohen’s D analysis. There was a significant effect of treatment on tryptophan hydroxylase 2 (TPH2) across the groups (p=0.019). E stimulated TPH2 expression and HFD prevented E-stimulated TPH2 expression (p<0.01). Treatment differentially affected monoamine oxidase B (MAO-B) across the groups (p=0.05). E increased MAO-B with LFD, and this stimulatory effect was prevented by HFD (p<0.05). There was a significant difference between treatments in corticotrophin releasing factor-receptor 2 (CRF-R2) expression (p=0.012). E increased CRF-R2 and this stimulatory effect was blocked by HFD (p<0.01). Regardless of diet, E increased Fev mRNA (p=0.028) and decreased CRF-receptor 1 (CRF-R1) mRNA (p=0.04). HFD suppressed urocortin 1 (UCN1; stresscopin) expression (p=0.045) but E treatment had no effect. Monoamine oxidase A (MAO-A) was different due to treatment across the groups (p=0.028). MAO-A was increased in the E+HFD group (p<0.01) whereas previous studies showed E suppressed MAO-A in macaques. The serotonin reuptake transporter (SERT), the serotonin 1A receptor (5HT1A), estrogen receptor beta (ERβ) and progestin receptor (PR) expressions were not different between groups. Estrogen receptor alpha (ERα) was undetectable. In summary, the data indicate that important actions of hormone therapy in the serotonin system may be lost in the context of a HFD.